Javents Lumbantobing, I Nyoman Suprapta Winaya, I Gede Putu Agus Suryawan - Lumbantobing, Javents; Suprapta Winaya, I Nyoman; Agus Suryawan, I Gede Putu (Teknik Desain Mekanika, 2021)
Abstract Waste has become a world problem, including for Bali. Starting from problems of environmental pollution, health, to affecting tourism. This research aims to destroy the pile of residual waste through thermal technology, namely incinerator. Incinerator is a technology capable of converting solid matter (waste) into gas and ash (bottom ash and fly ash). The operating temperature is an indicator in incinerator burning rate because it determines the quality of combustion in the reactor. This research was conducted by applying an experimental study that aims to determine the effect of incineration operating temperature on the burning rate of residual waste incinerator. The incinerator operating temperatures are varied, namely 300oC, 400 oC, 500 oC, and 600 oC. The results of this study indicate that the higher the operating temperature is used, the higher burning rete is obtained. The best of combustion rate occurs at an operating temperature of 600oC, ie 15.8 kg/h. Keywords: Incinerator, Burning Rate, Residual Waste, Operating Temperature